2016
DOI: 10.1186/s40064-016-2971-1
|View full text |Cite
|
Sign up to set email alerts
|

Motivation, students’ needs and learning outcomes: a hybrid game-based app for enhanced language learning

Abstract: In the context of European Higher Education students face an increasing focus on independent, individual learning—at the expense of face-to-face interaction. Hence learners are, all too often, not provided with enough opportunities to negotiate in the target language. The current case study aims to address this reality by going beyond conventional approaches to provide students with a hybrid game-based app, combining individual and collaborative learning opportunities. The 4-week study was carried out with 104… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 40 publications
(39 reference statements)
3
44
0
11
Order By: Relevance
“…Berns et al . () present and evaluate a hybrid game‐based app, which combines opportunities for individual learning with a collaborative game for the purpose of real‐life‐like communication in the studied language. Likewise, Hwang et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Berns et al . () present and evaluate a hybrid game‐based app, which combines opportunities for individual learning with a collaborative game for the purpose of real‐life‐like communication in the studied language. Likewise, Hwang et al .…”
Section: Resultsmentioning
confidence: 99%
“…Berns et al . () combined opportunities for both individual and collaborative language learning (vocabulary, grammar and communication practice to solve a murder mystery) through the use of a hybrid game‐based app; such a combination is seen to “motivate learners, stimulate perceived usefulness and added value, and better meet the language learning needs of today's language learners” (p. 19).…”
Section: Resultsmentioning
confidence: 99%
“…mosalingua.com/es/apps/), la mayoría de estas se centran en el aprendizaje individual del estudiante, sin aprovechar el potencial de los sistemas móviles para fomentar la colaboración e interacción entre múltiples usuarios en lengua meta (Burston, 2013;Palomo-Duarte, Berns, Cejas, Dodero y Caballero, 2016;Berns, Isla-Montes, Palomo-Duarte y Dodero, 2016). Sin embargo, en los últimos años se observa una tendencia a explotar el potencial educativo de apps colaborativas que promueven no solo la interacción y negociación entre múltiples usuarios sino también el trabajo de la competencia comunicativa a partir del uso escrito de la lengua meta.…”
unclassified
“…Lo que diferencia a esta app de otras es que obliga a sus usuarios a interactuar y negociar en lengua meta mediante un chat de texto implementado dentro de la propia app, permitiendo trabajar la competencia comunicativa. En términos de aprendizaje y motivación, los resultados indican que esta app, híbrida de tareas individuales y colaborativas, gozó de gran aceptación entre los estudiantes (Berns, Isla-Montes, Palomo-Duarte y Dodero, 2016).…”
unclassified
“…Several studies have investigated the affordances of mobile gaming and have reported mixed results of specifically designed games on the participants' language learning, though they may promote more interaction [38]. Most studies report positive student feedback on mobile gaming [39,40]. Others have suggested that mobile games can be effectively combined with content-integrated language learning activities [41] and that place-based mobile games are a great opportunity to connect students with local contexts [42].…”
Section: Introductionmentioning
confidence: 99%